The Gazebo - Grayson, Emily (New York : William Morrow, 1999)
A small-town newspaper editor stumbles upon a cache of tapes, letterss, and pictures telling the story of a doomed love affair.
Keywords: Separation (Psychology) -- Fiction; Social classes -- Fiction; Unrequited love -- Fiction; New York (State) -- Fiction; Love stories